45 to get j by itself you need to multiply both sides by 9
Answer:
7/4 * pi
Step-by-step explanation:
Area of circle = pi * r^2
Find radius:
pi * 49/64 = pi * r^2
49/64 = r^2
7/8= r
Circumference of circle = 2pi * r
2 * pi * (7/8) = 7/4 * pi
Assuming that the answer is in terms of pi as the question is in terms of pi
Answer:
it's too blurryyyyyyyyyyyyyyyyyyyyy
ANSWER
![{a}^{3} + {b}^{3} = (a + b)( {a}^{2 } - ab + {b}^{2} )](https://tex.z-dn.net/?f=%20%7Ba%7D%5E%7B3%7D%20%20%2B%20%7Bb%7D%5E%7B3%7D%20%3D%20%28a%20%2B%20b%29%28%20%7Ba%7D%5E%7B2%20%7D%20%20-%20ab%20%2B%20%20%7Bb%7D%5E%7B2%7D%20%29)
EXPLANATION
To find the expression that is equivalent to
![{a}^{3} + {b}^{3}](https://tex.z-dn.net/?f=%7Ba%7D%5E%7B3%7D%20%20%2B%20%7Bb%7D%5E%7B3%7D)
we must first expand
![{(a + b)}^{3}](https://tex.z-dn.net/?f=%20%7B%28a%20%2B%20b%29%7D%5E%7B3%7D%20)
Then we rearrange to find the required expression.
So let's get started.
![{(a + b)}^{3} = (a + b) {(a + b)}^{2}](https://tex.z-dn.net/?f=%20%7B%28a%20%2B%20b%29%7D%5E%7B3%7D%20%20%3D%20%28a%20%2B%20b%29%20%7B%28a%20%2B%20b%29%7D%5E%7B2%7D%20)
We expand the parenthesis on the right hand side to get,
![{(a + b)}^{3} = (a + b) ( {a}^{2} + 2ab + {b}^{2} )](https://tex.z-dn.net/?f=%20%7B%28a%20%2B%20b%29%7D%5E%7B3%7D%20%20%3D%20%28a%20%2B%20b%29%20%28%20%7Ba%7D%5E%7B2%7D%20%2B%202ab%20%2B%20%20%7Bb%7D%5E%7B2%7D%20%20%29)
We expand again to obtain,
![{(a + b)}^{3} = {a}^{3} + 3 {a}^{2}b + 3a {b}^{2} + {b}^{3}](https://tex.z-dn.net/?f=%20%7B%28a%20%2B%20b%29%7D%5E%7B3%7D%20%20%3D%20%20%7Ba%7D%5E%7B3%7D%20%20%2B%203%20%7Ba%7D%5E%7B2%7Db%20%2B%203a%20%7Bb%7D%5E%7B2%7D%20%20%20%2B%20%20%7Bb%7D%5E%7B3%7D%20)
Let us group the cubed terms on the right hand side to get,
![{(a + b)}^{3} = {a}^{3} + {b}^{3} + 3 {a}^{2}b + 3a {b}^{2}](https://tex.z-dn.net/?f=%20%7B%28a%20%2B%20b%29%7D%5E%7B3%7D%20%20%3D%20%20%7Ba%7D%5E%7B3%7D%20%20%20%2B%20%20%7Bb%7D%5E%7B3%7D%20%20%2B%203%20%7Ba%7D%5E%7B2%7Db%20%2B%203a%20%7Bb%7D%5E%7B2%7D%20)
![{(a + b)}^{3} = {a}^{3} + {b}^{3} + 3ab (a+ b)](https://tex.z-dn.net/?f=%20%7B%28a%20%2B%20b%29%7D%5E%7B3%7D%20%20%3D%20%20%7Ba%7D%5E%7B3%7D%20%20%20%2B%20%20%7Bb%7D%5E%7B3%7D%20%20%2B%203ab%20%28a%2B%20b%29)
We make the cubed terms the subject,
![{(a + b)}^{3} - 3ab (a+ b) = {a}^{3} + {b}^{3}](https://tex.z-dn.net/?f=%20%7B%28a%20%2B%20b%29%7D%5E%7B3%7D%20%20-%203ab%20%28a%2B%20b%29%20%3D%20%20%7Ba%7D%5E%7B3%7D%20%20%20%2B%20%20%7Bb%7D%5E%7B3%7D%20%20)
We factor to get,
![(a + b)({(a + b)}^{2} - 3ab ) = {a}^{3} + {b}^{3}](https://tex.z-dn.net/?f=%20%28a%20%2B%20b%29%28%7B%28a%20%2B%20b%29%7D%5E%7B2%7D%20%20-%203ab%20%29%20%3D%20%20%7Ba%7D%5E%7B3%7D%20%20%20%2B%20%20%7Bb%7D%5E%7B3%7D%20%20)
We expand the bracket on the left hand side to get,
![(a + b)( {a}^{2} + 2ab + {b}^{2} - 3ab ) = {a}^{3} + {b}^{3}](https://tex.z-dn.net/?f=%20%28a%20%2B%20b%29%28%20%7Ba%7D%5E%7B2%7D%20%20%2B%202ab%20%2B%20%20%7Bb%7D%5E%7B2%7D%20%20%20-%203ab%20%29%20%3D%20%20%7Ba%7D%5E%7B3%7D%20%20%20%2B%20%20%7Bb%7D%5E%7B3%7D%20%20)
We finally simplify to get,
Answer:
a.
Loan I's increase was 0.03 percentage points greater than Loan H's